A blended knowledge translation initiative to improve colorectal cancer staging [ISRCTN56824239] - Ryan David P; Klar Neil; Last Linda D; Law Calvin HL; Wright Frances C; Smith Andrew J (BMC, 2006)
Abstract Background A significant gap has been documented between best practice and the actual practice of surgery. Our group identified that colorectal cancer staging in Ontario was suboptimal and subsequently developed a knowledge translation strategy using the principles of social marketing and the influence of expert and local opinion leaders for colorectal cancer. Methods/Design Opinion leaders were identified using the Hiss methodology. Hospitals in Ontario were cluster-randomized to one of two intervention arms. Both groups were exposed to a formal continuing medical education session given by the expert opinion leader for colorectal cancer. In the treatment group the local Opinion Leader for colorectal cancer was detailed by the expert opinion leader for colorectal cancer and received a toolkit. Forty-two centres agreed to have the expert opinion leader for colorectal cancer come and give a formal continuing medical education session that lasted between 50 minutes and 4 hours. No centres refused the intervention. These sessions were generally well attended by most surgeons, pathologists and other health care professionals at each centre. In addition all but one of the local opinion leaders for colorectal cancer met with the expert opinion leader for colorectal cancer for the academic detailing session that lasted between 15 and 30 minutes. Discussion We have enacted a unique study that has attempted to induce practice change among surgeons and pathologists using an adapted social marketing model that utilized the influence of both expert and local opinion leaders for colorectal cancer in a large geographic area with diverse practice settings.